Is There a Consensus among Economists in the 1990's? - Alston, Richard M.; Kearl, J R; Vaughan, Michael (American Economic Review, 1992)
In a 1976 survey, Kearl et al. (1979; hereafter, 1976 survey) concluded that the then widespread perception that there was little agreement among professional economists on matters of theory or policy was simply wrong. However, the most casual empiricism, namely the continuing popularity of jokes about disagreements among economists, suggests the perception of noneconomists has not changed much since the 1970's. What is the present state of consensus among economists? This question is of interest because more than a decade has elapsed since the 1976 survey and during this time many issues confronting economists and the composition of the profession have changed.1 Benjamin M. Friedman and Lawrence H. Summers (1991 p. ix), for example, have asserted that ...economic thinking in many subfields of the discipline now differs markedly from what it was in 1970.... Consensus among European economists has been examined by Bruno S. Frey et al. (1984). Martin Ricketts and Edward Shoesmith (1990, 1992) focus exclusively on British economic opinion. This paper provides the first general analysis of opinions of U.S. economists in more than a decade. I. The Survey and Questionnaire